Serotonin Signals Modulate Mushroom Body Output Neurons for Sustaining Water-Reward Long-Term Memory in Drosophila - Lee, Wang-Pao; Chiang, Meng-Hsuan; Chang, Li-Yun; Shyu, Wei-Huan; Chiu, Tai-Hsiang; Fu, Tsai-Feng; Wu, Tony; Wu, Chia-Lin (Frontiers in Cell and Developmental Biology, 2021)
Memory consolidation is a time-dependent process through which an unstable learned experience is transformed into a stable long-term memory; however, the circuit and molecular mechanisms underlying this process are poorly understood. The Drosophila mushroom body (MB) is a huge brain neuropil that plays a crucial role in olfactory memory. The MB neurons can be generally classified into three subsets: γ, αβ, and α'β'. Here, we report that water-reward long-term memory (wLTM) consolidation requires activity from α'β'-related mushroom body output neurons (MBONs) in a specific time window. wLTM consolidation requires neurotransmission in MBON-γ3β'1 during the 0-2 hour period after training, and neurotransmission in MBON-α'2 is required during the 2-4 hour period after training. Moreover, neurotransmission in MBON-α'1α'3 is required during the 0-4 hour period after training. Intriguingly, blocking neurotransmission during consolidation or inhibiting serotonin biosynthesis in serotoninergic dorsal paired medial (DPM) neurons also disrupted the wLTM, suggesting that wLTM consolidation requires serotonin signals from DPM neurons. The GFP Reconstitution Across Synaptic Partners (GRASP) data showed the connectivity between DPM neurons and MBON-γ3β'1, MBON-α'2, and MBON-α'1α'3, and RNAi-mediated silencing of serotonin receptors in MBON-γ3β'1, MBON-α'2, or MBON-α'1α'3 disrupted wLTM. Taken together, our results suggest that serotonin released from DPM neurons modulates neuronal activity in MBON-γ3β'1, MBON-α'2, and MBON-α'1α'3 at specific time windows, which is critical for the consolidation of wLTM in Drosophila.